Kreativitas Guru PAI dalam Meningkatkan Pemahaman Fiqih di MA Unggulan K.H. Abd. Wahab Hasbulloh Tambakberas Jombang - Siti Nor Khabibatul Khoiriyah; Waslah Waslah; Emi Lilawati (ANWARUL, 2026)
Fiqh learning in madrasahs requires teacher creativity so that material can be delivered in a more contextual, engaging, and easily understood manner, especially in facing the dynamics of learning in the digital era. This study aims to describe the creativity of Islamic Religious Education (PAI) teachers, identify the learning methods used, and analyze supporting and inhibiting factors in improving students’ understanding of Fiqh at MA Unggulan K.H. Abd. Wahab Hasbulloh Bahrul Ulum Tambakberas Jombang. This study used a qualitative approach with a case study design. The research subjects consisted of the Fiqh teacher and the madrasah principal, who were selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the creativity of PAI teachers is reflected in the use of various learning methods, such as lectures, discussions, group presentations, direct practice, video demonstrations, poster creation, and learning projects. Teachers also utilize digital facilities, such as classroom televisions, students’ laptops, and social media, to strengthen the learning process. The main supporting factor is the availability of digital facilities, while the inhibiting factors include power outages and Wi-Fi network disruptions. The conclusion of the study affirms that the creativity of PAI teachers plays an important role in improving students’ understanding of Fiqh learning. The implications of this study indicate the need to strengthen teachers’ digital competence, provide more stable learning facilities, and develop alternative strategies so that Fiqh learning can continue to take place effectively, actively, and meaningfully.